The Nutritive and Immunoprotective Quality of Human Milk beyond 1 Year Postpartum: Are Lactation-Duration-Based Donor Exclusions Justified?. (August 2013) - Perrin, Maryanne Tigchelaar; Fogleman, April; Allen, Jonathan C.
Donor human milk is critical for the fragile preterm infant who does not have access to his or her mother's milk, improving survival rates and quality of survival and decreasing hospital stay. Despite the opening of donor milk banks around the world, shortages continue as demand for donor milk exceeds supply. One potential means of increasing supply is by reducing exclusion criteria that prohibit mothers from donating milk based on duration of lactation. Minimal research has been done on the composition of human milk during the second year of lactation, with most research focusing on the nutritive compounds and not the immunoprotective compounds. Several immunoprotective compounds, including lysozyme, lactoferrin, secretory immunoglobulin A, and oligosaccharides, are abundant in human milk compared to bovine-based infant formula and are partially or fully retained during Holder pasteurization, making them an important differentiating feature of donor milk. A PubMed search was conducted to review studies in human milk composition during the second year of lactation. Limitations of existing research include sample collection protocols, small study sizes, and use of populations that may have been at risk for nutritional deficiencies. Stable concentrations of several components were reported including protein, lactose, iron, copper, lactoferrin, and secretory immunoglobulin A. Lysozyme concentration increased during extended lactation, while zinc and calcium concentrations declined into the second year. Conflicting findings were reported on fat content, and no information was available regarding oligosaccharide content. More research is needed to create evidence-based guidelines regarding the nutritive and immunoprotective value of donor milk throughout the course of lactation.